PENGARUH BUDAYA PERUSAHAAN TERHADAP KINERJA KARYAWAN PT. WAHANA SUN MOTOR SEMARANG - Faizal Nur Rahman; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2019)
The Culture that exist in a company will influence how the way of employee work and how the employee behave and have same perspective in doing work activities. Culture of the company have impact in the efficiency and effectiveness of the company. Based on data obtained from PT. Wahana Sun Motor Majapahit Semarang, it shows fluctuating performance appraisal from 2016-2018. This is certainly a loss for PT. Wahana Sun Motor Majapahit Semarang if not immediately repaired, considering that PT. Wahana Sun Motor Majapahit Semarang always wants improved employee performance. The local HRD/GA said that there was an impact of the unfavorable application of corporate culture on employee performance. The statement is in line with the results of the preliminary study which states that there are indications of performance fluctuations caused by the culture of the company. Through the results of the preliminary study it can be seen that there are indications of performance fluctuations caused by coorporate culture. PT. Wahana Sun Motor Majapahit Semarang is a company that moved in a distribution of vehicle sales and after sale service. PT. Wahana Sun Motor Majapahit Semarang adjust 5 company culture such as integrity, responsible, cooperative, business harmony and continuous learning and improvement. The type of this research is explanatory research with 26 employee as respondent. The technique of collecting data is questionnaire, observation, and literature review. The Technique of analysis are validation test, reliability of the correlation coefficient, coefficient of determination, simple and multiple linear regression, t arithmetic and F arithmetic. From the analysis that already done variable integrity has a correlation coefficient of 0.478, variable responsible has 0,739, variable cooperative has 0,647, variable business harmony has 0,561, variable continuous learning and improvement has 0,641, and variabel company culture has 0,858. Coefficient of determination integrity has 22,8 %, responsible has 54,7 %, cooperative has 41,9%, business harmony has 31,5 % and continuous learning and improvement has 41,1 %. Simple regression test integrity gave positive effect of 0,293, responsible has 0,633, cooperative has 0,510, business harmony has 0,757, continuous learning and improvement has 0,326 and company culture has 0,737.. Simultaneously, integrity, responsible, cooperative, business harmony,and continous learning and improvement take effect with employee performance with F-Count (5,975) > F-Table (2,71) with significance number 0,002 < 0,005. The conclusion from this research is variable company culture take effect with the employee performance of PT. Wahana Sun Motor Majapahit Semarang. The suggestions is the company should be raise the attention towards company culture especially in responsible variable and continous learning and improvement so in the end it will give good effect on employee performance.